2014
DOI: 10.4081/nursrep.2014.3225
|View full text |Cite
|
Sign up to set email alerts
|

Pain management after lung surgery

Abstract: Pain management is an integral challenge in nursing and includes the responsibility of managing patients’ pain, evaluating pain therapy and ensuring the quality of care. The aims of this study were to explore patients’ experiences of pain after lung surgery and evaluate their satisfaction with the postoperative pain management. A descriptive design was used which studied 51 participants undergoing lung surgery. The incidence of moderate postoperative pain varied from 36- 58% among the participants and severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, there are several corresponding findings from previous national publications using SCQIPP. Approximately one‐third of the patients experience more pain than was expected and nearly 90% were moderately to very satisfied with the post‐operative analgesic regime [15,16]. Compared with Idvall et al .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, there are several corresponding findings from previous national publications using SCQIPP. Approximately one‐third of the patients experience more pain than was expected and nearly 90% were moderately to very satisfied with the post‐operative analgesic regime [15,16]. Compared with Idvall et al .…”
Section: Discussionmentioning
confidence: 94%
“…In post-operative pain management, the Strategic and Clinical Quality Indicators in Postoperative Pain Management (SCQIPP), a binary questionnaire, has been developed and validated in Sweden [10,11]. Previous research in Sweden with SCQIPP has specified participating inpatients in orthopaedic, thoracic, lung, vascular and abdominal surgical care as well as less specified 'general surgery' [12][13][14][15][16]. In addition, Vatansever and Akansel [17] validated SCQIPP for the Turkish context with the inclusion of 113 patients, and Milutinović et al [18] assessed the quality of health care in managing acute postoperative pain by a modified and translated Serbian version including 135 patients; both studies included a vast variety of surgical areas.…”
Section: Introductionmentioning
confidence: 99%
“…can cause fatigue; thus, the assessment of postoperative pain and management of the pain is the most important nursing intervention (Frodin & Stomberg, 2014). The score the participants gave for the quality of care given for pain relief during the postoperative period was higher than the average (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that among 51 patients who underwent lung surgery, moderate postoperative pain occurred in 36-58% of cases and severe pain occurred in 11-26% of cases; furthermore, 39% of patients experienced more pain than expected. 4 Pain is not only an extremely uncomfortable experience but can also lead to a variety of physical and psychological complications such as increased oxygen consumption and pulmonary complications, 5 as well as depression, anxiety, sleep disorders, and social disorders. 6 Pain also is one of the main factors that affects early ambulation in patients after surgery, which can hinder their rapid recovery.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that among 51 patients who underwent lung surgery, moderate postoperative pain occurred in 36–58% of cases and severe pain occurred in 11–26% of cases; furthermore, 39% of patients experienced more pain than expected. 4 …”
Section: Introductionmentioning
confidence: 99%